Flatness pattern recognition of ultra-wide tandem cold rolling mill - BAO Ren-ren; ZHANG Jie; LI Hong-bo; JIA Sheng-hui; LIU Hai-jun; XIAO Sheng (工程科学学报)
A cubic flatness pattern expressed by Legendre orthogonal polynomial was introduced to build a new flatness pattern recognition model,in which least squares regression was used. Using the new model,flatness pattern recognitions of 2180 mm CVC ultra-wide cold rolling mill and 1550 mm UCM common wide tandem cold rolling mill were carried out. The results show that the main flatness error of the strip produced by the ultra-wide mill is "OS cubic waves" considering the cubic flatness pattern,and "quarter waves" without the cubic pattern; the main flatness error of the strip produced by the common wide mill is "central waves" whether considering the cubic flatness pattern or not,therefore the necessity of introducing cubic flatness pattern for the new recognition model is verified. Finally,potential application of the new model in the asymmetric flatness control of ultra-wide tandem cold rolling mill is discussed.